Lifelong religion as habitus : religious practice among displaced Karelian orthodox women in Finland - Kupari, Helena. (Numen Book Series, 2016)
In this book, Helena Kupari examines the lived religion of Finnish, evacuee Karelian Orthodox women through an innovative reading and application of Pierre Bourdieu's practice theory. After the Second World War, Finland ceded most of its Karelian territories to the Soviet Union. Over 400,000 Finns, including two thirds of the Finnish Orthodox Christians, lost their homes. This book traces the ways in which the religion of Orthodox women was affected by their displacement and their experiences as members of the Orthodox minority in post-war and contemporary Finland. It contributes to theoretical discussions on lived religion by producing an account of lifelong minority religion as habitus, or an embodied and practical "sense of religion".